Host Invasion to Immune Evasion: Emerging Concepts in Pathogen Virulence Strategies - Alisha Arzoo (International Journal of Pathogens, 2025)
Pathogens have evolved a wide repertoire of virulence strategies that allow them to invade host tissues, establish infection, and circumvent immune responses. From the initial steps of adhesion and colonization to complex molecular mimicry, antigenic variation, and immunomodulation, pathogens display remarkable adaptability. While traditional research has emphasized host cell entry and toxin production, emerging evidence highlights subtler and more dynamic strategies such as manipulation of host signaling pathways, subversion of phagocytosis, and exploitation of the microbiome. Viral, bacterial, fungal, and parasitic pathogens each deploy unique yet overlapping tactics, often orchestrated through genetic plasticity, secretion systems, and regulatory networks. Understanding these mechanisms is critical in an era marked by rising antimicrobial resistance, zoonotic spillovers, and pandemics. This review synthesizes current knowledge on pathogen virulence from invasion to immune evasion, integrating classical concepts with cutting-edge insights from molecular biology, genomics, and immunology. By examining diverse pathogens from Staphylococcus aureus and Mycobacterium tuberculosis to influenza virus and Plasmodium falciparum we highlight shared evolutionary pressures and unique survival tactics. The article concludes by discussing implications for vaccine development, therapeutic targeting, and future research directions, underscoring the urgent need to translate mechanistic insights into clinical and public health interventions.
Keywords: Emerging infectious diseases; Host–pathogen interaction; Microbial pathogenesis; Virulence factors; immune evasion